Allelopathic potential and an allelopathic substance in mango leaves - Masahiko Suzuki; Md Sirajul Islam Khan; Arihiro Iwasaki; Kiyotake Suenaga; Hisashi Kato-Noguchi (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2017)
The present study was aimed to determine the allelopathic potential of mango (Mangifera indica L.) leaves and to identify allelopathic substances in the leaves. The aqueous methanol extracts of mango leaves inhibited seedling growth of garden cress, radish, rapeseed, foxtail fescue and crabgrass, and the inhibitory effects increased with the increasing extract concentration, suggesting that mango leaves may contain allelopathic substances. The extract was then purified by several chromatographic runs through a bioassay-directed fractionation, and an growth inhibitory substance was isolated and identified by spectral data as methyl-3,4,5-trihydroxybenzoate (methyl gallate). Methyl gallate at the concentration of 10 mM inhibited 98.6% and 99.8% of root and shoot growth of garden cress relative to the control, respectively, and 94.4% and 49.3% of those of foxtail fescue, respectively. The concentrations of methyl gallate required for 50% growth inhibition (I50) on garden cress roots and shoots were 3.9 and 3.3 mM, and those on foxtail fescue roots and shoots were 1.5 and 9.5 mM, respectively. It is the first report of an allelopathic substance in mango leaves and allelopathic activity of methyl gallate. Therefore, the mango leaves may have potential as a soil additive material for the weed management options.